Longevity, lifestyles and eating The importance of education - Petretto, Donatella Rita; Pili, Roberto (UNICApress, 2021)
Since the last decades of the 20th century, there have been an increasing attention on the ageing of population and on the need to develop specific interventions aiming to promote wellbeing and quality of life of ageing individuals (Petretto et al., 2016, 2017, 2018, Pili and Petretto, 2019). World Health Organization (WHO) considered the development of those interventions as a priority and asked countries to create a research and intervention agenda with a focus on the promotion of healthy and active ageing. According to a biopsychosocial approach, WHO defined some pillars at the base of healthy and active ageing. Moreover, WHO focused their attention on eating and healthy lifestyles as ways to promote wellbeing and longevity (WHO, 2002, WHO, 2012, Paul et al., 2012). There are increasing research findings in this field, also by cross-national comparisons and by the development of intervention models aimed to prevent "not-communicable disorders" and to promote wellbeing.